Climate change disclosure and carbon performance of Chinese listed companies: exploring the moderating effects of climate governance and corporate environmental governance - Zhang, Sailu (Frontiers in Climate, 2024)
Climate change poses numerous risks to businesses, leading to growing attention from governments and stakeholders toward corporate climate change disclosures. However, whether these disclosures can effectively drive companies to enhance their carbon reduction efforts remains an urgent question. Using panel data from heavily polluting companies in China, this study employs generalized structural equation modeling (GSEM) to empirically examine the moderating effects of government-level climate governance and corporate-level environmental governance on the relationship between climate change disclosure and carbon performance. The results indicate that the interaction between climate governance and climate change disclosure significantly promotes improvements in carbon performance, whereas the impact of corporate environmental governance is comparatively limited. These findings underscore the critical role of government-driven climate governance in enhancing the effectiveness of climate change disclosures and provide practical recommendations for policymakers and corporations to improve climate disclosure practices and advance carbon reduction efforts.